Improvement of the Frying Quality and Storage Stability of the Sudanese Groundnut Oil - Mohammed Ali, Dena Omer; R. Ahmed, Abdel Halim; Mohammed, Babiker E. (Pakistan Journal of Nutrition, 2011)
The improvement of the frying quality and storage stability of the groundnut oil by adding 30% palm olein were studied during the frequent frying and different storage periods: 12 days, 40 days and 96 days at room temperature (37±3oC). The physiochemical parameters used in this study showed significant (p